The Role of Zionist Leaders in the Global Clash of Civilizations: An Analytical Study: دور قادة الصهيونية في صدام الحضارات العالمي: دراسة تحليلية - Hamda Miftah ‘Isa Ma’tuq al-Tamimi,; Mohd Nor, Mohd Roslan; Mohammad Abdelhamid Salem Qatawneh, (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2025)
This research aims to study the role played by the leaders and thinkers of the Zionist movement in fueling the global clash of civilizations, and to analyze this role in light of successive global events, starting with the psychological barrier between Islamic civilization and Western civilization, and to exploit that to bring the West closer together and work to ensure that the West and the Jews are in An anti-Islamic team, and then Zionism’s acquisition of Muslim land in Palestine and the establishment of a national homeland for them, in addition to the West’s full, continuous and unconditional support for the Zionist entity in Palestine, and ensuring its security and stability, which came after a long period of efforts by Zionist leaders to defuse the conflict, And work to stimulate it, Reaping the fruits of this in what we are witnessing in the events of the wars of the Arab-Israeli conflict in general, and what is happening recently in the war on Gaza, and the bloody and genocidal practice that the Zionist entity is practicing in full view of the countries of the West, and the full support of the United States despite its claims - falsely - of civil and humanitarian Motherhood and childhood care, and other bright slogans. However, the role of Zionist leaders is apparent in this Western thought, as if the war between Islam and Christianity was the result of an artificial clash between the Islamic and Western civilizations.